Perjalanan Karir Kesenimanan Siti Chairani Proehoeman Sebagai Penyanyi Soprano (Sebuah Biografi) - Kumala, Ofa Yutri Kumala Yutri; Martarosa, Martarosa; Nursyirwan, Nursyirwan (UNIVERSITAS INDO GLOBAL MANDIRI)
This research, is the career journey of Siti Chairani Proehoeman as a soprano who has taken part in various countries, and is a great teacher who is a role model for every student who specializes in studying in the field of sound art. Siti Chairani Prohoeman is an Indonesian citizen who is very influential in Malaysia, he created a movement about vocals in Malaysia, great enthusiasm Siti Chairani Proehoeman has made vocals a culture for Malaysia. The names of the countries that Siti Chairani Proehoeman often performed at concerts, operas and recitals are in Italy, Germany, the Netherlands, France, Finland, USA, Japan, South Korea, Thailand, Singapore, Malaysia, Indonesia. Siti Chairani Proehoeman already has several serial albums and her professional career is a Classical / Opera singer (Soprano). The factors of Siti Chairani Proehoeman became a famous soprano in various countries, namely family background, habits, environment and education. This study discusses Siti Chairani Proehoeman's career as a soprano in a biographical form. In this case the history of Siti Chairani Proehoeman's career as a soprano based on data, sources, informants and all matters relating to the life history of an artist. This research method, analytic description, case study, observer participation. The results showed that, in the practice of Siti Chairani Proehoeman's life based on a musicalological perspective and assisted through historical and biographical reviews, Siti Chairani Proehoeman's position was a famous soprano.